The Importance of Working Conditions for Interpreters - Lina Farsia; Hanum Muziatun Nahriah (ACCENTIA: Journal of English Language and Education, 2021)
This paper discusses about the importance of working conditions for interpreters. A literature review is used as an approach for this paper. For the past years, the employers have not taken the working conditions for interpreters into account. This paper mentions three aspects of working conditions that have to be paid full attention in order for the interpreters to do their job professionally: physical wise, emotional wise, and financial wise. The employers needs to provide these three aspects for the interpreters to produce good outcome.